Control interno a la gestión administrativa y su incidencia en las contrataciones de bienes y servicios en el gobierno autónomo descentralizado parroquial rural San Jacinto del Búa. periodo 2020 – 2021 - Arias Ojeda, Glenda Elizabeth (2022)
Internal control is a process aimed at promoting the efficiency and effectiveness of the financial administrative operations of an entity. The general objective of this research project is to evaluate the incidence of internal control on administrative management in the contracting of goods and services of the San Jacinto del Búa Autonomous Decentralized Rural Parish Government, during the period 2020-2021. The purpose of this study is to become a useful tool for decision-making and the proper application of the internal control system. The methodology used was exploratory and descriptive, inductive, deductive, analysis, and synthesis methods were used, which allowed addressing the current problem for analysis and study. The sample was applied to all the servers in the financial administrative area. The collection of information was carried out through techniques such as a questionnaire, a survey adapted to the Likert model applied to officials, an interview addressed to the highest authority and observation in order to collect data, which were then tabulated, analyzed and interpreted to obtain the results that were illustrated graphically and served to establish the conclusions of the present investigation. The main findings of the study show that there is a deficient planning and evaluation of the plans, programs and resources that the entity possesses, as well as the inadequate control of the administrative processes for the acquisition of goods and/or services, causing the objectives set are not being carried out effectively